Minor Structural Alterations of the Vocal Fold Cover: Vocal Quality before and after Treatment - Brito,Tatiany Cíntia da Silva (2021)
Abstract Introduction Minor structural alterations of the vocal fold cover are important causes of dysphonia. The variability in the type of alteration and the grade of vocal deviation affects the definition of the conduit and the results of treatment. Objective To characterize the occurrence, the selected treatments adopted and vocal quality before and after treatment in patients with minor structural alterations of the vocal folds cover. Methods This was a cross-sectional study based on the records of patients treated by an interdisciplinary team at the laryngology outpatient clinic of a public university hospital from 2010 to 2018. Data collection consisted of access to a database of information on otorhinolaryngological diagnostic hypotheses, intervention and perceptual-auditory vocal assessments before and after the treatment. Data from 102 subjects were analyzed. Association tests were applied between the perceptualauditory vocal results and the different alterations found and between these and the adopted treatments. The results of the degrees of vocal deviation before and after treatment were also compared. Results The degree of roughness was associated with the sulcus vocalis, and in this alteration the highest occurrence was mild degree of roughness. There was an improvement in the breathiness and general grade of vocal deviation after treatment. Conclusion Cysts were the most frequent structural alteration in the population studied. There was an association between the degree of general deviation and that of roughness in sulcus vocalis cases. The breathiness and the general grade of vocal deviation improved after treatment regardless of the type of treatment and alteration.